PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVA SDN 163 PEKANBARU - Putri, Dita Permata; Witri, Gustimal; ', Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research was social studies students achievement in fourth graderes (IVA) SDN 163 Pekanbaru still low with average value 61,62 (with KKM 70). The purpose of this research was to improve the students achievement of the fourth graderes (IVA) SDN 163 Pekanbaru. with the implementation of Problem Based Learning model. This research was an classroom action research with two cycles in second semester 2014/2015. Before implementation Problem Based Learning modelaverage 61,62,after implementation of Problem Based Learning model, UH I was 70,81 that improve 14,91% from before exam with average 61,62. UH II was 80,40 that improve 30,48%. Teacher’s activities with the implementation of Problem Based Learning model at first meeting of first cycle was 55% (enough category), and second meeting was 65% (good category) that improve 10 point. At second cycle, theacher’s activities at first meeting was 80% (good category) that improve 15 point from second meeting of first cycle. Second meeting of second cycle was 90% (verygood category) which improve 10 point. Students activites at first meeting of first cycle was 55% (enough category), and second meeting 70% (good category) that improve 15 point. At second cycle, students activities at first meeting was 80% (good category) that improve 10 point from second meeting of first cycle. Second meeting of second cycle was 95% (verygood category) which improve 15 point. Implementation of Problem Based Learning model can improved social studies students achievement of fourth graderes (IVA) SDN 163 Pekanbaru.Key Words: Problems Based Learning, Sosial Studies Student’s Achievement